Desain dan Simulasi Elemen Hingga Gantry Crane Kapasitas 9 Ton Menggunakan Autodesk Inventor 2017 - Lasinta Ari Nendra Wibawa (Politeknik Manufaktur Negeri Bangka Belitung, 2019)
Currently, the gantry crane in LAPAN Garut still uses steel material. The steel material is protected using a coating to minimize the impact of corrosion. However, this method is less efficient, considering the corrosion rate in LAPAN Garut is very high because it is located on the coast of Cilauteureun. It also creates problems in terms of maintenance because it has to be done regularly and periodically repainting. In addition, not all equipment is available maintenance funds every year. The objective of this paper is to design and analyze the stress of a gantry crane with a capacity of 9 tons using Aluminum 6061 material. The material used is three units of JIS G 3192 H standard frame (I-shape) with a size of 150 x 150 x 7 mm, four units of JIS G 3466 frame (square profile) with a size of 150 x 150 x 6 mm, and four units of JIS G 3466 frame (square profile) with a size of 125 x 125 x 6 mm. Finite element analysis is performed using Autodesk Inventor Professional 2017 software. The simulation results show that the gantry crane has a mass, von Mises stress, deformation, and safety factors respectively at 165.36 kg; 132.9 MPa; 13.67 mm; and 2.07.